Antioxidant Activity Of Leilem Leaf Extract Fractions Clerodendrum minahassae Teijsm. and Binn. Using The DPPH Method (2,2-Diphenyl-1-Picrylhydrazil) - Imrawati, Imrawati; Utami, Yuri Pratiwi; Hardianto, Hardianto (International Journal of Health Sciences, 2023)
Clerodendrum minahassae Teijsm. and Binn plant is included in the Clerodendrum genus which contains chemicals such as alkaloids, flavonoids, phenols, tannins and steroids which have an important role in the development of medicine, including as antioxidants, anti-inflammatory, anti-diabetic and antibacterial. This study aims to determine the antioxidant activity of leilem leaf fractions using the DPPH method. Leilem leaves were extracted using the maceration method using 70% ethanol, then partitioned using the liquid-liquid extraction method using three different solvents, namely n-hexane, ethyl acetate and water. The fraction of the partition was then tested for antioxidant activity using the DPPH method and its absorbance was measured using a UV-VIS spectrophotometer with a wavelength of 515 nm. The research results showed that the n-hexane fraction had an IC50 value of 185.704 ppm, the ethyl acetate fraction had an IC50 value of 105.357 ppm and the water fraction had an IC50 value of 549.258 ppm with the IC50 value of the quarcetin comparison being 8.86 ppm. It can be concluded that the highest antioxidant activity is found in the ethyl acetate fraction, which is included in the moderate antioxidant category.